IL-17A Alone Weakly Affects the Transcriptome of Intestinal Epithelial Cells but Strongly Modulates the TNF-α–induced Expression of Inflammatory Mediators and Inflammatory Bowel Disease Susceptibility Genes. Issue 9 (7th August 2014) - Friedrich, Matthias; Diegelmann, Julia; Beigel, Florian; Brand, Stephan
Abstract : Background: In contrast to anti-TNF-α antibodies, anti-IL-17A antibodies lacked clinical efficacy in a trial with patients suffering from Crohn's disease. We therefore analyzed how IL-17A modulates the inflammatory response elicited by TNF-α in intestinal epithelial cells (IEC). Methods: Target mRNA levels in IEC and colonic biopsies were assessed by RNA microarray and quantitative real-time PCR. Signaling pathways were analyzed using receptor neutralization and pharmacological inhibitors. Target protein levels were determined by immunoblotting. Results: Microarray analysis demonstrated that IL-17A alone is a weak inducer of gene expression in IEC (29 regulated transcripts), but significantly affected the TNF-α–induced expression of 547 genes, with strong amplification of proinflammatory chemokines and cytokines (>200-fold increase of CCL20, CXCL1, and CXCL8). Interestingly, IL-17A differentially modulated the TNF-α–induced expression of several inflammatory bowel disease susceptibility genes in IEC (increase of JAK2 mRNA, decrease of FUT2, ICAM1, and LTB mRNA). Negative regulation of ICAM-1 by IL-17A was verified on protein level. The significance of these findings is emphasized by inflamed lesions of patients with inflammatory bowel disease demonstrating significant correlations ( P < 0.01, Rho, 0.57–0.85) for JAK2, ICAM1, and LTB mRNA with IL17A and TNF mRNA. Conclusions: Our study demonstrates the modulation of inflammatory bowel disease susceptibility gene mRNA in IEC as a novel important property of IL-17A. Given the weak impact of sole IL-17A stimulation on IEC target gene expression, our study provides an important explanation for the lack of clinical efficacy of sole IL-17A neutralization, but suggests a beneficial effect of combined IL-17A/TNF-α that is currently in clinical development.